Rectal Cancer : A Mini Literature Review - I.A.Trisna Kumala Dewi; Soehartati A. Gondhowiardjo (Radioterapi & Onkologi Indonesia, 2021)
Colorectal cancer is one of the most common cancer in the world. In Indonesia, as reported in Globocan 2018, colorectal cancer is number eight by cancer site in term of incidence, mortality, and prevalence. It also number five of new cases in 2018. it started  proximally at rectosigmoid junction which is as high as third sacral and extending to anorectal ring, just proximal to dentate line. In general, the upper third is located intraperitoneally and the lower two-thirds of the rectum extraperitoneally. The most common histopatology found in rectal cancer is adenocarcinoma. The etiology  of  rectal  cancer  is believed to be  multifactorial,  including  both  genetic  and  environmental  factors. Hematochezia is the most common presenting symptom in rectal cancer. diagnostic tool of rectal cancer is divided into invasive and non invasive examination. The simplest method of recognizing is digital rectal examination that can detect around 70 % of rectal cancer. TNM classification is used as a standard to evaluate the extend of tumour. Surgery alongside with radiation therapy and chemotherapy play an important role as main treatment modality of rectat cancer. In radiotherapy, if 2D technique preferred, 3 fields that consist of posterior-anterior (PA) field and opposing lateral fields are the most commonly used. If 3D technique preferred, 3D conformal radiotherapy (3DCRT) is more recommended than   intensity-modulated radiation therapy (IMRT). For postoperative the radiation treatment is conventional  fractionation to a total dose of  45 Gy to the entire pelvis, followed  by  a boost of  5.4 Gy  to the tumor bed. For neoadjuvant therapy,  conventional  fractionation to a total dose of 45 Gy to tdioteraphe entire pelvis, followed by a boost of 5.4 Gy to the tumor bed is recommended.